Diseño de Herramienta para la Evaluación Financiera de Micro, Pequeños y Medianos Emprendimientos del Sector Servicios. - García Orjuela, Diego Ferney; Suarez Caro, Laura Katherine (Universidad Antonio Nariño, 2021)
The average net business entry rate in Colombia is 1.1%, this means that, for every 100 companies, 19 enter the formal market and approximately 18 leave (Confecámaras, 2018). Of these, 32% correspond to enterprises that have not completed more than two years, known as Star Ups. According to figures from the Cámara de Comercio de Bogotá (CCB, 2018), the lack of profitability is the main cause of business discontinuity, which caused 37.5% of business closures during 2018. This situation led to the following problem: How to generate a tool for making financial decisions for micro, small and medium enterprises in the service sector?